“A Rose for the Russian Orthodox Church”: An Account of the Pro Oriente Foundation’s Trip to the Soviet Union in 1980 - Beljakova, Nadežda Alekseevna (The journal of Eastern Christian studies, 2023)
The article studies the unofficial trip of Cardinal Franz König, the head of the Catholic Church of Austria and Roman cardinal. In November 1980, König initiated a ten-day tour through the USSR for a delegation of 30 people – board members of the Pro Oriente Foundation (focused on developing communication with the Eastern Churches). The tour was presented as a pilgrimage, not an official visit. But König’s being the Archbishop of Vienna, and therefore on the list of Austria’s highest state officials, gave this trip a political and diplomatic component. The article is based on materials collected in the archive of Cardinal König, oral history interviews and diaries. The privately organized trip raises the question of the degree to which the “Iron Curtain” was impenetrable for the representatives of the Catholic world, especially at a time of increasing international complexity following the development of the Solidarity movement in Poland and the Soviet invasion of Afghanistan. The focus of the article is on the symbolic meaning of trips around the Soviet Union and how they were presented in the media for the various “Western” religious circles and especially in the Austrian media. This trip seems likely to illustrate Cardinal Franz König’s concept that Vienna would be a bridge between the churches of the West and the East. The article attempts to show the specific diplomatic, ecclesiastical and touristic dimensions of this trip.